2018
DOI: 10.1177/0003489418820871
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Mortality After Endoscopic Sinus Surgery for Invasive Fungal Rhinosinusitis

Abstract: Objectives: Invasive fungal rhinosinusitis is a rare, life-threatening condition that affects the paranasal sinuses. The standard of care after diagnosis includes surgical debridement and aggressive medical management. Despite treatment, mortality remains unacceptably high. Most data are derived from small cohort experiences, with limited identification of mortality risk factors in the acute setting. The authors used a large national database to better understand clinical factors associated with inpatient mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
(34 reference statements)
2
19
0
1
Order By: Relevance
“…The presence of atypical organisms was not associated with worse outcomes in our patient population. A recent large database study by Burton et al 5 found that the presence of Mucor was associated with a higher inpatient mortality, similar to our findings that patients with Mucor/Rhizopus had a higher mortality (76.4%) compared with patients with Aspergillus alone (66.7%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The presence of atypical organisms was not associated with worse outcomes in our patient population. A recent large database study by Burton et al 5 found that the presence of Mucor was associated with a higher inpatient mortality, similar to our findings that patients with Mucor/Rhizopus had a higher mortality (76.4%) compared with patients with Aspergillus alone (66.7%).…”
Section: Discussionsupporting
confidence: 91%
“…4,8,10,11 The literature is confounded among publications, reporting diabetes as both a negative 10 and positive prognostic factor. 5,7 Our study found diabetic patients to have a mortality of 76% compared with 47% in nondiabetic patients, therefore supporting its association with poor outcome. We went onto further investigate whether or not the presence of multiple immunosuppressant comorbidities was associated with worsened outcomes and found that mortality rates increased with an increasing number of comorbidities.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Раніше мукормікоз реєстрували надзвичайно рідко у порівнянні з аспергільозом чи кандидозом. Однак, в останні роки частота випадків мукормікозу має тенденцію до зростання як в Україні, так і в інших країнах [11,12,13,14,15]. Також у групі ризику щодо контакту зі спорами пліснявих грибів знаходяться працівники галузі сільського господарства або мікробіологічної промисловості.…”
Section: вступunclassified